2000
DOI: 10.1063/1.373391
|View full text |Cite
|
Sign up to set email alerts
|

Behavior of μMAG standard problem No. 2 in the small particle limit

Abstract: For a uniformly magnetized rectangular particle with dimensions in the ratio 5 : 1 : 0.1, the coercive and switching fields in the (1, 1, 1) direction are determined to be Hc/Ms = 0.057069478 and Hs/Ms = 0.057142806. Previous micromagnetic computations of coercive and switching fields that did not approach these values for small particles are analyzed. It is shown that the disagreement was primarily due to a disparity in the method of calculating demagnetization energy. Corrected simulations are shown to agree… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
0

Year Published

2002
2002
2013
2013

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(24 citation statements)
references
References 9 publications
1
23
0
Order By: Relevance
“…A comparison of such measurements with the theoretical demagnetizing factors [6] showed clearly that the averaging causes a loss of information, because the actual magnetization processes, such as the nucleation or elimination of domains, depend on the local field. This result is not surprising, since it has been noted [10] a decade ago, and later emphasized [11] with all the fine details, that numerical computations of the magnetostatic energy must include averaging the field over the discretization unit. Using instead the value of the demagnetizing field at the centre of that unit, leads to considerably different results.…”
mentioning
confidence: 89%
“…A comparison of such measurements with the theoretical demagnetizing factors [6] showed clearly that the averaging causes a loss of information, because the actual magnetization processes, such as the nucleation or elimination of domains, depend on the local field. This result is not surprising, since it has been noted [10] a decade ago, and later emphasized [11] with all the fine details, that numerical computations of the magnetostatic energy must include averaging the field over the discretization unit. Using instead the value of the demagnetizing field at the centre of that unit, leads to considerably different results.…”
mentioning
confidence: 89%
“…Hence, the reliability of this code cannot be tested by the Mag standard problems of the National Institute of Standards and Technology of which focuses are three-dimensional finite bodies. 38,39 Instead, we observed that our self-written code successfully reproduces the domain wall structure given in Fig. 3 of Ref.…”
Section: Computational Detailsmentioning
confidence: 47%
“…However, the computation overhead and management of resources become major issues in FEM simulations. To compare different numerical solvers, the Micromagnetic Modeling Activity Group (µMag) publishes standard problems for micromagnetism [17]- [19]. A more recent addition included the effects of spin transfer torque [20].…”
Section: Introductionmentioning
confidence: 99%